Post-traumatic Stress, Work Performance and Employee Satisfaction Among Health Care Workers during the COVID-19 Pandemic - Fatma Kantaş Yilmaz, Saadet Karakuş (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: This cross-sectional study was carried out to investigate post-traumatic stress, work performance and employee satisfaction of healthcare workers (HCWs) (nurses and physicians) during the COVID-19 pandemic. Methods: A face-to-face questionnaire was administered to 169 HCWs working in inpatient clinics of two public hospitals in İstanbul, Türkiye. The questionnaire comprised four parts, including a socio-demographic form, the Impact of Event Scale-Revised (IES-R), the Employee Performance Scale and the Employee Satisfaction Scale (ESS). Results: IES-R scores showed that 14.2% and 47.9% of participants experienced mild and severe post-traumatic stress (PTSD), respectively. IES-R total and all sub-dimensions scores (intrusion, avoidance, and hyperarousal) were significantly higher in participants who worked ≥48 hours a week and in those who were exposed to verbal/physical violence. EPS scores showed weak inverse correlations with the overall IES-R score (r=-.300; p=.000) and with all sub-dimension scores, while ESS scores (r=,528; p=,000) showed moderate correlations with the overall EPS score and strong correlations with all sub-dimension scores. Conclusions: The remarkably higher incidence of PTSD showed a close relationship with both satisfaction and performance levels among HCWs. As PTSD has long-term effects on the lives of HCWs as well as on quality of life, preventive interventions directed to the sources of PTSD in the work environment are of utmost importance and should encompass attempts to promote both satisfaction and work performance, and to establish safe working conditions.